Modelling the habitat suitability of rattan (Calamus zollingeri) in Lore Lindu National Park, Central Sulawesi - Maarif, Fadjri; Basoka, Muh. Darmawan; Santoso, Aji Rachmat; Sitinjak, Richo Nandhito (Jurnal Penelitian Kehutanan Wallacea, 2024)
Calamus zollingeri is a potential rattan species that is widely used by the community and is found in the Sulawesi region. As one of the potential non-timber forest products, habitat suitability modelling is needed to determine the distribution and prediction of C. zollingeri distribution in Lore Lindu National Park (LLNP), Central Sulawesi. This study used a species distribution modelling approach with the Maximum Entrophy method. C. zollingeri encounter data were obtained through data collected in the Lore Lindu Management Information System (SIMRELI) from 2019 to 2023. Environmental variables used in the modelling included NDVI, altitude, slope, land cover and distance from river. The modelling results show that 40% of the total LLNP area is highly suitable for C. zollingeri habitat, 20% of the total LLNP area is suitable for C. zollingeri habitat, and 40% of the total LLNP area is unsuitable/insufficient data. This study is important as a reference material for the management of LLNP, especially in structuring the management zone of LLNP.